Starch molecular fine structure is associated with protein composition in chickpea seed. (15th November 2021) - Tan, Xiaoyan; Tan, Xinle; Li, Enpeng; Bai, Yeming; Nguyen, Thoa T.L.; Gilbert, Robert G.
Abstract: Chickpea ( Cicer arietinum L.) seed is a nutritional food high in starch and protein. This study aims to find the relationships between the molecular fine structure of starch and the composition of storage proteins and metabolic enzymes, using different chickpea varieties. It is found that storage proteins and starch biosynthetic enzymes influence each other. The initial formation of amylopectin molecules is affected by storage proteins, as suggested by the positive correlation (p < 0.01) between the average molecular size of amylopectin and total protein content. In addition, a higher amount of seed globulin could be an indication of higher amylose content and more short – medium amylose chains (degree of polymerization, DP, 118–2000). This study might assist selection of chickpea varieties with desirable qualities, such as low starch digestibility. Graphical abstract: Unlabelled Image Highlights: Storage proteins are involved in starch biosynthesis and molecular fine structure. Total protein content is positively correlated with amylopectin molecular size. Higher globulin content indicates higher amylose content. This can aid variety selection for desirable properties such as slow digestion.